2015
DOI: 10.19104/jepm.2015.110
|View full text |Cite
|
Sign up to set email alerts
|

A Prevalence Study of the Activities of Daily Living (ADL) Dependency among the Elderly in Four Districts in Selangor, Malaysia

Abstract: Introduction: Similar to many other developing countries worldwide, Malaysia is currently experiencing a demographic transition towards an ageing population. This situation leads to an increasing number of disabled individuals in the population. The present study investigated the epidemiology of activities of daily living (ADL) dependency among the elderly in one of the highest urbanized state in Malaysia i.e. the state of Selangor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In our study, we observed that the level of dependence rate was 43.3% with severe dependency at 2.5% which is consistent with the findings of Puteh et al . [ 1 ] in Malaysia where the prevalence of severe and total dependency was at 1.1% each. According to a study carried out in two randomly selected urban wards of Dibrugarh city, Assam, 34.7% of participants had limitations in one or more ADL items.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we observed that the level of dependence rate was 43.3% with severe dependency at 2.5% which is consistent with the findings of Puteh et al . [ 1 ] in Malaysia where the prevalence of severe and total dependency was at 1.1% each. According to a study carried out in two randomly selected urban wards of Dibrugarh city, Assam, 34.7% of participants had limitations in one or more ADL items.…”
Section: Discussionmentioning
confidence: 99%
“…This being a natural process of dynamic biological changes, is influenced by variables other than chronological aging such as social construction, which defines its reality and meaning. [ 1 ] It is a known fact that elderly people in India are growing rapidly as life expectancy is increasing. According to the 2011 census, elderly population constitute about 8.6% of the total Indian population which is likely to grow further to about 20% by 2050.…”
Section: Introductionmentioning
confidence: 99%
“…However, this leads to reliance on the healthier older adults to carry out activities. Studies conducted in Malaysia on the prevalence of daily activities among seniors in four districts in Selangor indicated that good social support from good partners is associated with a high risk of dependency [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Malaysia, Act 685, which is the Persons with Disabilities Act 2008, defines a person with a disability as an individual who has a long-term physical, mental, intellectual or sensory impairment that interacts with various limitations that may affect participation in the community [ 6 ]. People with disabilities often require support and may have a greater need for assistance with household tasks, as well as increased levels of care if they reside in residential aged care homes or hospitals [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation